Analysis of Consumers’ Willingness to Pay for Ginger Sugar Herbal Drinks and Its Determining Factors - Ainun Niha , Aevita; Rahmad, Nuraini (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Increasing competition in the herbal beverage industry has prompted MSMEs producing ginger sugar herbal beverages to improve product quality. The implementation of this measure is expected to increase production costs and selling prices, necessitating an analysis of consumer willingness to pay. This study aims to determine the price limit that consumers are willing to pay and the factors that influence Willingness to Pay. This study involved 100 respondents selected based on purposive sampling. The analysis methods used in this study include descriptive analysis, Contingent Valuation Method (CVM), and Logistic Regression. The results show that consumers are predominantly women, aged 17–35 years, employed as students, with a monthly income in the range of IDR 2,000,001 – IDR 4,000,000, a bachelor's degree or equivalent, a consumption pattern of 1–2 times per week, and a reason for consumption that is a healthy lifestyle. The maximum average Willingness to Pay value is IDR 19,305.56, which is 37.9% higher than the current price of IDR 14,000 per package. The analysis shows that consumer characteristics simultaneously have a significant effect on Willingness to Pay, with the dominant factors including gender, consumption pattern, and reason for consumption.